2022
DOI: 10.3389/fphys.2022.901164
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regular aerobic exercise on renal function in patients with CKD: A systematic review and meta-analysis

Abstract: Objective: To evaluate the effect of regular aerobic exercise on the improvement of renal function in patients with chronic kidney disease through meta-analysis and to provide targeted exercise recommendations for patients with CKD.Methods: PubMed, Web of Science, EBSCO, China National Knowledge Infrastructure (CNKI), and other databases were searched, and randomized controlled trials on the effects of regular aerobic exercise on renal function-related indexes in patients with CKD were collected according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recently, Ma et al reported a meta-analysis of 12 RCTs, comprising 410 patients with CKD; the results indicated that regular aerobic exercise significantly improves the estimated GFR (eGFR), and the levels of serum creatinine, daily urinary protein excretion, and serum urea nitrogen in CKD patients. Further, a single exercise session of more than 30 min was associated with significantly improved eGFR (p < 0.01), including walking and running, but not cycling, as exercise modalities were associated with significantly improved serum creatinine levels (p < 0.05) in CKD patients (Figures 2 and 3) [35]. Thus, regular aerobic exercise has beneficial effects on the eGFR (especially with durations longer than 30 min), serum creatinine (especially with walking or running as the modality), daily urinary protein excretion, and blood urea nitrogen levels in CKD patients [35].…”
Section: Chronic Effect Of Exercise In Pre-dialysis Patients With Ckdmentioning
confidence: 94%
“…Recently, Ma et al reported a meta-analysis of 12 RCTs, comprising 410 patients with CKD; the results indicated that regular aerobic exercise significantly improves the estimated GFR (eGFR), and the levels of serum creatinine, daily urinary protein excretion, and serum urea nitrogen in CKD patients. Further, a single exercise session of more than 30 min was associated with significantly improved eGFR (p < 0.01), including walking and running, but not cycling, as exercise modalities were associated with significantly improved serum creatinine levels (p < 0.05) in CKD patients (Figures 2 and 3) [35]. Thus, regular aerobic exercise has beneficial effects on the eGFR (especially with durations longer than 30 min), serum creatinine (especially with walking or running as the modality), daily urinary protein excretion, and blood urea nitrogen levels in CKD patients [35].…”
Section: Chronic Effect Of Exercise In Pre-dialysis Patients With Ckdmentioning
confidence: 94%
“…In contrast to moderate-intensity exercise, strenuous exercise of long-duration and/or high intensity can negatively impact intestinal health, as it reduces intestinal blood flow and increases intestinal permeability, leading to impaired gut-barrier function, depressed immune function, and increased risk for viral and bacterial infections [ 64 , 65 ]. While in the general population evidence suggests that regular moderate-to-vigorous aerobic physical activity reduces the risk of gastrointestinal malignancies [ 66 ], diabetes [ 67 ], chronic kidney disease [ 68 , 69 ], fatty liver disease [ 70 ], and gut microbial dysbiosis [ 71 ], little is known about the impact of strenuous physical exercise on the gastrointestinal tract in SOTRs.…”
Section: Organ Systems At Riskmentioning
confidence: 99%
“…There is growing evidence for the utilisation of exercise-based therapeutic options in the role of prevention and delayed progression of CKD. Recently published research [17,18] pertaining to the potential benefits for people at this early stage in the CKD patient pathway does reinforce the need…”
Section: Self-management and Predialysis Interventionsmentioning
confidence: 99%
“…There is growing evidence for the utilisation of exercise-based therapeutic options in the role of prevention and delayed progression of CKD. Recently published research [ 17 , 18 ] pertaining to the potential benefits for people at this early stage in the CKD patient pathway does reinforce the need to focus on commissioning exercise-based rehabilitation as part of any prevention package, as well as the keen desire for exercise-based rehabilitation for people approaching end-stage care.…”
Section: Introductionmentioning
confidence: 99%